Pemilihan Supplier Sepatu dan Tas dengan Menggunakan Metode AHP (Analytical Hierarchy Process) dan MAUT (Multi Attribute Utility Theory) - Aulia Nur Afifah; Bekti Nugrahadi; Yunita Primasanti (Pusat Riset dan Inovasi Nasional, 2024)
Toko Sehati is a business in selling leather shoes and bags. The decline in Toko Sehati sales was caused by reducing buyer interest due to the addition of new suppliers, from A and B, to A, B, C, D, E. The study aims to determine the appropriate shoe and bag supplier using the AHP (Analytical Hierarchy Process) and MAUT (Multi Attribute Utility Theory) methods. This study used the criteria of time, price, service, flexibility, and quality. Based on the AHP method, it shows that the weight of the time criteria is 0.053, price 0.113, service 0.162, flexibility 0.209, and quality 0.462. Calculations using the AHP method indicates that the highest value at supplier C with a value of 0.454, supplier A with a value of 0.199, supplier B with a value of 0.192, supplier D with a value of 0.111, and supplier E with a value of 0.040. Meanwhile, the calculation using the MAUT method shows that the highest value for supplier C with a value of 0.916, supplier A with a value of 0.810, supplier B with a value of 0.662, supplier D with a value of 0.643, and supplier E with a value of 0. The recommended supplier order based on calculations using a combination of the AHP and MAUT methods is supplier C, A, B, D, E.